Pengaruh Lokasi, Kualitas Pelayanan, dan Cita Rasa Terhadap Keputusan Pembelian Konsumen Mie gacoan - Yumie Amanda; Sahrul Musarof; Ayu Rianti Rosyadi; Aprista Damayanti; Rifkhan Rifkhan (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of location, service quality, and taste imagery on consumer purchasing decisions at Mie Gacoan Tangerang Bumi Indah under PT Pesta Pora Abadi. The fierce competition in the culinary sector requires companies to understand crucial factors driving consumer decisions. This research used a quantitative method with a survey approach. Data were gathered by distributing questionnaires to 100 consumers via purposive sampling. Data analysis was performed through validity, reliability, classical assumption, and multiple linear regression tests using SPSS. The descriptive statistics results showed that location (3.86), service quality (3.67), and taste (3.90) were rated well by respondents. Based on the regression analysis, location ( = 0.436, p = 0.005) and taste (  = 0.242, p = 0.050) have a positive and significant partial effect on purchasing decisions, while location and taste simultaneously exert a significant impact. This study provides strategic insights for culinary firms to optimize accessibility, maximize consistent taste preferences, and adjust strategic layouts to boost purchasing decisions.